Vertical transmission of HIV among pregnant women who initially had false–negative rapid HIV tests in four South African antenatal clinics - Mayaphi, Simnikiwe H. (PLoS One, 2019)
INTRODUCTION: There is a risk of mother-to-child transmission of HIV (MTCT) during pregnancy and breastfeeding. The aim of this study was to assess vertical transmission of HIV among pregnant women who initially had false–negative rapid HIV tests in South African antenatal care (ANC) clinics. METHODS: Pregnant participants were enrolled in a diagnostic study that used nucleic acid amplification testing (NAAT) to screen for early HIV infection among individuals who tested negative on rapid HIV tests used at the point-of-care (POC) facilities. Participants were enrolled from four ANC clinics in the Tshwane district of South Africa. All NAAT-positive participants were recalled to the clinics for further management. Vertical transmission was assessed among exposed infants whose HIV polymerase chain reaction (PCR) results were available. RESULTS: This study enrolled 8208 pregnant participants who tested negative on rapid HIV tests between 2013 and 2016. Their median age was 26 years (interquartile range [IQR]: 23–30). NAAT detected HIV infections in 0.6% (n = 49; 95% confidence interval CI: 0.5–0.8) of all study participants. The distribution of these infections among the four clinics ranged from 0.3%– 1.1%, but this was not statistically significant (p = 0.07). Forty-seven participants (95.9%) were successfully recalled and referred for antiretroviral treatment initiation as part of prevention of MTCT (PMTCT). Most women with newly diagnosed HIV infection presented for the first ANC visit in the second (61.9%, n = 26) and third (31.0%, n = 13) trimesters. HIV PCR results were available for thirty-two infants, three of whom tested positive (9.4%; 95% CI: 1.98–25.02). CONCLUSIONS: This study showed that supplemental HIV testing for pregnant women led to earlier linkage to the PMTCT programme. Inaccurate diagnosis of HIV infection at ANC clinics is likely to undermine the efforts of eliminating MTCT particularly in HIV-endemic settings.